Low-temperature pyrolysis of polyethylene - Ishmiev, I.I.; Aldangurova, A.U.; Khalikova, Z.S.; Aldabergenova, S.K.; Fomin, V.N.; Dik, A.V.; Batkov, P.A. (Ye.A.Buketov Karaganda State University Publish hous, 2016)
This article describes the commodity polyethylene pyrolysis at temperatures 300–370 ºC. It was shown that the yield of gaseous products in these conditions increases with increasing temperature and by prolonging the process. Dependencies are described by using stochastic determinated design of experiments. The formal activation energy of the pyrolysis process (7.7 kJ/mol) with producing gaseous components was also determined.
Полиэтиленнің төмен температуралы пиролизі
Низкотемпературный пиролиз полиэтилена
Keywords: stochastic determinated design of experiment; polyethylene pyrolysis; one-way ANOVA